How to write a narrative literature review article ? - Saracci, Chiara; Mahamat, Maryam; Jacquerioz, Frederique (Revue medicale suisse, 2019)
Narrative overviews of scientific literature contribute to the updating and critique of available medical knowledge. Indirectly, they help to formulate new research projects based on the synthesis and interpretation of the results of a non-systematic selection of published studies. To facilitate both optimal reading and synthesis of studies we deem useful to propose a standardized approach to the various steps of the development and writing of a narrative literature overview.